Serum Calprotectin Level Is Independently Associated With Carotid Plaque Presence in Patients With Psoriatic Arthritis - Cheng, Isaac T.; Meng, Huan; Li, Martin; Li, Edmund K.; Wong, Priscilla C.; Lee, Jack; Yan, Bryan P.; Lee, Alex P. W.; So, Ho; Tam, Lai-Shan (Frontiers in Medicine, 2022)
Background Whether calprotectin could play a role in augmenting cardiovascular (CV) risk in patients with psoriatic arthritis (PsA) remains uncertain. The aim of this study is to elucidate the association between serum calprotectin level and subclinical atherosclerosis in patient with PsA. Method Seventy-eight PsA patients (age: 52±10 years, 41 [52.6%] male) without CV disease were recruited into this cross-sectional study. Carotid intima-media thickness (cIMT) and the presence of plaque were determined by high-resolution ultrasound. Calprotectin levels in serum were quantified by enzyme-linked immunosorbent assay. The variables associated with the presence of carotid plaque (CP) were selected from the least absolute shrinkage and selection operator (LASSO) regression analysis. Results 29/78 (37.2%) of patient had carotid plaque (CP+ group). Serum calprotectin level was significantly higher in the CP+ group (CP- group: 564.6 [329.3-910.5] ng/ml; CP+ group: 721.3 [329.3-910.5] ng/ml, P=0.005). Serum calprotectin level correlated with PsA disease duration (rho=0.280, P=0.013) and mean cIMT (rho=0.249, P=0.038). Using LASSO regression analysis, the levels of Ln-calprotectin (OR: 3.38, 95% CI [1.37, 9.47]; P=0.026) and PsA disease duration (OR: 1.09, 95% CI [1.01, 1.18]; P=0.013) were screened out from a total of 19 variables. The model in predicting the presence of CP was constructed by Ln-calprotectin and PsA disease duration with an area under the receiver-operating characteristic (ROC) curve of 0.744, (95 CI% [0.59, 0.80], P=0.037). Conclusion Serum calprotectin level is associated with the presence of CP in PsA. Further studies are required to confirm whether this pathway is associated with CV events in PsA.